2013
DOI: 10.1158/0008-5472.can-12-4196
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Herpesvirus HHV-8 Promotes Androgen-Independent Prostate Cancer Growth

Abstract: Mechanisms underlying progression to androgen-independent prostate cancer following radical ablation therapy remain poorly defined. Although intraprostatic infections have been highlighted as potential cofactors, pathogen influences on pathways that support tumor regrowth are not known. To explore this provocative concept, we derived androgen-sensitive and -insensitive prostate epithelial cells persistently infected with human herpesvirus 8 (HHV-8), an oncogenic herpesvirus that has been detected in normal pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
(50 reference statements)
1
12
0
1
Order By: Relevance
“…The downregulation of MSP was previously described in the context of rhinovirus infection [28]. MYGATT et al [29] reported virus-mediated silencing of MSP, which seems in accordance with our findings. Finally, significant upregulation of CCL7 has been observed in mice infected with rhinovirus [20] and in children during infection by different respiratory viruses, including RSV [30].…”
Section: Discussionsupporting
confidence: 93%
“…The downregulation of MSP was previously described in the context of rhinovirus infection [28]. MYGATT et al [29] reported virus-mediated silencing of MSP, which seems in accordance with our findings. Finally, significant upregulation of CCL7 has been observed in mice infected with rhinovirus [20] and in children during infection by different respiratory viruses, including RSV [30].…”
Section: Discussionsupporting
confidence: 93%
“…But recently HHV-8 has been detected in prostate epithelial cells and was implicated in prostate cancer in several studies [26,27] [28]. Therefore, HHV-8 may be able to infect epithelial mammary cells and may cause mammary cells transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation for discrepant findings is differences in the distribution of PCa cases by stage across study populations, as HHV-8 was recently shown to confer the capacity for androgen-independent growth in androgen-sensitive PCa cells in vitro (28). This finding suggests that HHV-8 may play a role in late-stage PCa progression to androgen-independent disease rather than or in addition to earlier stages of PCa development.…”
Section: Discussionmentioning
confidence: 99%